Agama dan Politik: Perbandingan Sosio-Historis Antara Konteks Indonesia dan Kerajaan Israel Bersatu - Moru, Osian Orjumi (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2022)
The purpose of this article is to describe various forms of formalization, interpretation, and concretization of the relationship between religious and political entities that are integralistic, intersectional, or secular in the context of Indonesia and the United Kingdom of Israel. The approach used to describe the above is a hermeneutic approach through literature study. The results of the study show that the relationship between religious and political entities, both in the context of the Indonesian state and the context of the United Kingdom of Israel is an intersectional and integralistic relationship. The model and the nature of these relations are clearly seen in the pattern and process of selecting the head of government, the elaboration of ideology and the basis of the state, such as in the formation of Pancasila and the J source, to the concretization of forms of community social interaction which are always related to socio-religious dynamics. At this point, although the state of Indonesia and the United Kingdom of Israel have different contexts and concepts of government, the relationship between religious and political entities is a form of reciprocal relationship and reflects the concept of idealistic culture. Tujuan penulisan artikel ini adalah mendesripsikan berbagai bentuk formalisasi, intepretasi, maupun konkretisasi hubungan antara entitas agama dan politik yang bersifat integralistik, intersectional, ataupun sekularistik baik pada konteks Indonesia maupun Kerajaan Israel Bersatu. Pendekataan yang digunakan untuk mendeskripsikan perihal di atas adalah pendekatan hermeneutik melalui studi kepustakaan. Hasil penelitian menunjukan bahwa relasi antara entitas agama dan politik baik pada konteks negara Indonesia maupun konteks Kerajaan Israel Bersatu merupakan relasi yang bersifat intersectional dan integralistik. Model dan sifat relasi tersebut terlihat jelas dalam pola dan proses pemilihan kepala pemerintahan, elaborasi ideologi dan dasar negara seperti dalam pembentukan Pancasila dan sumber Y, sampai pada bentuk-bentuk konkritisasi interaksi sosial masyarakat yang selalu berhubungan dengan dinamika sosial-keagamaan. Pada titik ini, meski negara Indonesia dan Kerajaan Israel Bersatu memiliki perbedaan konteks dan konsep pemerintahan, namun ralasi antara entitas agama dan politik menjadi bentuk relasi yang resiprokal dan mencerminkan konsep idealistic culture.